The remote cruise method for the robot with multiple sensors. (March 2018) - Lin, Chern-Sheng; Huang, Yen-Chen; Chen, Chung-Ting; Lin, Yue-Der; Chen, Pei-Chi
Highlights: The robot can cruise on a flexible route with remote cruise control. This system can avoid obstacles automatically. The robot is remotely controlled to reach the ward to record the patient's condition. The cruise operation can be performed both on a fixed route and the shortest path. The turning angle for avoidance is calculated with the innovative virtual wall estimation. Abstract: Remote cruise control for care robot is proposed in this study, the robot module and virtual wireless network are integrated into a computer, and the robot is combined with multiple light sensors, a laser displacement module and CCD camera, which enable the robot to cruise on a flexible route. The cruise operation can be performed both on a fixed route and the shortest path. The central monitoring room can master any unexpected situation met during the cruise, track the object, avoid dead angles through many monitors, automatically avoid collisions, and can distinguish the outline of obstacles. If it meets a wall, it automatically corrects its direction and walks parallel to the wall. If it meets an irregular obstacle, the turning angle for avoidance is calculated by using the innovative virtual wall estimation in order to cruise autonomously.